Pharmacological Properties and Therapeutic Applications of Acalypha indica: Review Article (Journal of Pharma Insights and Research, 2025)
Acalypha indica, a medicinal plant native to tropical and subtropical regions, has significant value in traditional medicine systems across Asia and Africa. The plant contains various bioactive compounds including alkaloids, flavonoids, tannins, and saponins that contribute to its therapeutic properties. Modern pharmacological studies show its potential in treating various ailments through antibacterial, anti-inflammatory, antioxidant, anticancer, antidiabetic, and wound-healing activities. The plant's leaves, roots, and aerial parts exhibit prominent biological effects, with the leaves showing particular potential in antimicrobial and anti-inflammatory applications. Recent investigations have shown mechanisms of action for several therapeutic properties, including prostaglandin-mediated analgesic effects and cytokine-modulated wound healing. Clinical studies indicate potential applications in managing diabetes, skin conditions, and respiratory disorders. While traditional uses are extensively studied, standardization of extracts and detailed toxicological profiling remain areas requiring further research. Modern analytical techniques have identified key compounds like acalyphamide and acalyphine, providing molecular information about the plant's biological activities. This review presents current evidence on pharmacological properties, phytochemical composition, and therapeutic applications of A. indica.